HISTOPATHOLOGIC PATTERN OF BLADDER CANCERS IN IBADAN SOUTHWEST NIGERIA: AN UPDATE - Takure, AO (J West Afr Coll Surg, 2015)
BACKGROUND: A study from the University College Hospital, Ibadan, Southwest, Nigeria on bladder cancers had described an increase in the frequency of urothelial carcinoma compared to the earlier reported preponderance of squamous-cell carcinoma. AIM: To provide an update on the histopathologic pattern of bladder cancers in our community and to explore its implications for future health system policies. METHODS: The records of the Ibadan Cancer Registry from January 1997 to December 2014 were reviewed and the data analyzed for the histologic subtypes of bladder cancers diagnosed in the hospital. RESULTS: Two hundred and sixteen bladder tumours were recorded during this period with a male to female ratio of 3.2:1. Complete information was available in 195 cases of which 181 (96.8%) were bladder carcinomas whilst 14 were sarcomas. Of the bladder carcinomas, 68.5%, 19.9% and 11.6% were urothelial carcinomas, squamous cell carcinomas, and adenocarcinomas (AC) respectively. Urothelial carcinoma was more common in all age groups and its peak age of occurrence was in the 51-60 year age group. The peak age for squamous cell carcinoma was in the 41-50 year age group. Mean and median age of occurrence was significantly lower in females in the urothelial and squamous cell carcinomas, but lowest in squamous cell carcinoma [P = < 0.0001]. CONCLUSION: This population study has confirmed urothelial carcinoma as the predominant histotype of bladder cancer in Ibadan, Southwest Nigeria currently and that both urothelial and squamous cell carcinomas occur earlier in women.